2020
DOI: 10.1002/lary.28621
|View full text |Cite
|
Sign up to set email alerts
|

The Nasal Swell Body and Septal Perforation Repair

Abstract: Objectives: To review our experience with secondary surgery for persistent nasal obstruction following successful septal perforation repair and describe the potential contribution of the nasal swell body (NSB) to obstruction. Study Design: Retrospective chart review. Methods: IRB-approved retrospective chart review of perforation repairs utilizing bilateral mucosal flaps performed by the senior author from October 2008 through April 2019 was performed. Patients who underwent secondary surgery for persistent na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Perforation repairs utilizing bilateral nasal mucosal flaps with an interposition graft have the theoretical advantage, over other techniques, of using both physiologic nasal mucosa and a third tissue layer as a barrier to re-perforation. Various interposition graft materials have been successfully used and include temporalis fascia, 5,7,10 temporoparietal fascia, 2,3 costal perichondrium, 4 cartilage (septal, auricular, costal), 1,5 septal bone, human acellular dermis, 11 and porcine small intestine submucosa. 12 Kridel and Delaney 13 opined that the choice of graft material was less important to repair success than the achievement of a bilateral, tension-free closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforation repairs utilizing bilateral nasal mucosal flaps with an interposition graft have the theoretical advantage, over other techniques, of using both physiologic nasal mucosa and a third tissue layer as a barrier to re-perforation. Various interposition graft materials have been successfully used and include temporalis fascia, 5,7,10 temporoparietal fascia, 2,3 costal perichondrium, 4 cartilage (septal, auricular, costal), 1,5 septal bone, human acellular dermis, 11 and porcine small intestine submucosa. 12 Kridel and Delaney 13 opined that the choice of graft material was less important to repair success than the achievement of a bilateral, tension-free closure.…”
Section: Discussionmentioning
confidence: 99%
“…Septal perforation repair is performed endonasally through a right hemitransfixion incision. 6,7 Mucoperichondrial/periosteal elevation is performed bilaterally. The extent of elevation and incision placement for bipedicle flap development is determined by perforation size and position.…”
Section: Methodsmentioning
confidence: 99%
“…The senior author performed all perforation repairs with a technique using bilateral mucosal flaps with an autogenous interposition graft. 4,5 The open approach was used early in this experience for selected perforations. Subsequently, all repairs were performed through an endonasal approach.…”
Section: Methodsmentioning
confidence: 99%
“…18 A recent retrospective study found that repairing SPs with bilateral mucosal flaps may cause persistent postoperative nasal congestion due to NSB and that nasal congestion in these patients may be relieved by the surgical reduction of NSB without reperforation. 10 Application of isolated topical decongestants in NSB can determine whether surgery is needed and help predict nasal patency after surgery. 41 A silastic sheet was cut into the shape and size of the anterior nasal cavity.…”
Section: Surgical Attemptsmentioning
confidence: 99%
“…5,6 The NSB has been a surgical target of interest and hence surgical procedures have also been attempted to reduce its volume in recent years. [7][8][9][10] Nevertheless, the structure and function of NSBs are still far less understood. 11,12 Therefore, we endeavored to produce a precise contemporary description to improve our understanding of NSB.…”
Section: Introductionmentioning
confidence: 99%